Performance of single and mixed rhizobial inoculants on nodulation, dry matter and seed yield of lentil (Lens culinaris) - Bhuiyan, MAH; Khanam, D; Rahman, MT; Sheikh, MHR; Bhuiyan, MMH (Bangladesh Journal of Agricultural Research, 2014)
Field experiments were carried out at Regional Agricultural Research Station (RARS), Ishurdi, Pabna during the rabi season of 2005-06 and 2006-07 to find out the effectiveness of Rhizobium strains for achieving higher yield of lentil, the variety BARI Masur4. There were six treatments that were Rhizobium strains- BARI RLc-104, BARI RLc-105, BARI RLc-106, BARI RLc107, mixed culture of the four strains, and control (no Rhizobium). The experiment was designed in randomized complete block having 4 replications of each treatment.The rhizobial inocula were peat based and used @ 1.5 kg/ha. A basal dose of P @ 22 kg/ha, K @ 42 kg/ha, S @ 20 kg/ha, and @ 5 kg Zn/ha was used for all treatments. The highest nodule number (11.7/plant in 2006 and 10.3/plant in 2007) and dry nodule weight (10.53 mg/plant in 2006 and 9.58 mg/plant in 2007) were found with mixed culture. Mixed culture produced the highest seed yield in 2006 (1.36 t/ha, 37.4% higher over uninoculated control) and in 2007, BARI RLc-104 recorded the highest seed yield (1.23 t/ha, 60.3% higher over uninoculated control). However, all the strains including mixed culture had similar seed yields over the years. DOI: http://dx.doi.org/10.3329/bjar.v39i1.20147 Bangladesh J. Agril. Res. 39(1): 105-112, March 2014